Fatigue behavior of uncorroded butt welded joints made of bridge weathering steel. (April 2020) - Su, Han; Wang, Jian; Du, Jinsheng
Abstract: Bridge weathering steel produced in China has been employed in bridges worldwide, among them Q345qNH is the most commonly used steel grade. Fatigue behavior of uncorroded butt welded joints made of bridge weathering steel Q345qNH was explored in this paper. Fatigue tests were conducted on 13 specimens involving 9 stress ranges, S-N curve and its lower bound of 95% survival probability were established. It was observed that the design S-N curve for butt welded joint in Eurocode 3 is suitable for fatigue assessment of this batch of specimens and provides a considerable safety margin. Numerical simulation of mixed-mode fatigue crack propagation and analytical investigation of fatigue crack propagation were conducted, it was found that numerical simulation is preferred since it considers the variation in stress due to crack propagation. The influences of initial crack size, initial crack shape, initial crack location and angular misalignment of plates on fatigue behavior of butt welded joints were investigated, the expression between fatigue life and initial crack size was derived. Additionally, it is recommended that a semi-elliptical crack with initial crack depth of 0.2 mm and initial aspect ratio of 1/4 to be adopted when information on initial crack is unavailable. The fatigue test results provide reference for fatigue design of steel bridges made of coated weathering steel and serve as control for analysis of deterioration of fatigue behavior due to corrosion for corroded butt welded joints made of uncoated weathering steel.